2017
DOI: 10.3390/rel8080134
|View full text |Cite
|
Sign up to set email alerts
|

Do Religious Struggles Mediate the Association between Day-to-Day Discrimination and Depressive Symptoms?

Abstract: Although numerous studies have shown that discrimination contributes to poorer mental health, the precise mechanisms underlying this association are not well understood. In this paper, we consider the possibility that the association between day-today discrimination (being disrespected, insulted, and harassed) and depressive symptoms is partially mediated by religious struggles (religious doubts and negative religious coping). To test our mediation model, we use data collected from the 2011 Miami-Dade Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 79 publications
3
19
0
1
Order By: Relevance
“…Contrastingly, those without these attributes tend to engage in negative religious coping. Among the general population, Pargament et al’s dually focused conception of religious coping has found broad empirical support with respect to both positive (Acavedo, Ellison, and Xu 2014; Bradshaw and Ellison 2010; Head and Thompson forthcoming; Stroope et al 2017) and negative forms of religious coping (Hill et al 2017; Park, Wortmann, and Edmondson 2011). While these findings highlight religious coping broadly, there are several key components of religion that may be salient for the mental well-being of inmates: moralistic emotion management, personal control and mastery, and social support.…”
Section: Empirical and Theoretical Considerationsmentioning
confidence: 99%
“…Contrastingly, those without these attributes tend to engage in negative religious coping. Among the general population, Pargament et al’s dually focused conception of religious coping has found broad empirical support with respect to both positive (Acavedo, Ellison, and Xu 2014; Bradshaw and Ellison 2010; Head and Thompson forthcoming; Stroope et al 2017) and negative forms of religious coping (Hill et al 2017; Park, Wortmann, and Edmondson 2011). While these findings highlight religious coping broadly, there are several key components of religion that may be salient for the mental well-being of inmates: moralistic emotion management, personal control and mastery, and social support.…”
Section: Empirical and Theoretical Considerationsmentioning
confidence: 99%
“…Consistent with prior research (Hill, Christie-Mizell, Vaghela, Mossakowski, & Johnson, 2017), exploratory factor analyses were conducted with varimax rotation and the factor loadings (> 0.42) Consistent with prior research (Hill, Christie-Mizell, Vaghela, Mossakowski, & Johnson, 2017), exploratory factor analyses were conducted with varimax rotation and the factor loadings (> 0.42)…”
Section: Independent Variablesmentioning
confidence: 98%
“…Responses included: 1 (never), 2 (rarely), 3 (sometimes), 4 (often), and 5 (very often). Consistent with prior research (Hill, Christie-Mizell, Vaghela, Mossakowski, & Johnson, 2017), exploratory factor analyses were conducted with varimax rotation and the factor loadings (> 0.42)…”
Section: Independent Variablesmentioning
confidence: 99%
“…Moreover, perceived discrimination during the transition to adulthood can have detrimental effects on mental health (i.e., depression and anxiety symptoms) decades later (Assari 2017). Discrimination, in part, contributes to poorer health by exposing individuals to trauma, stress, structural strain (perceptions of structural and institutional barriers), and maladaptive coping styles (Ahmed, Mohammed, and Williams 2007; Hill et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%